2022
DOI: 10.3138/jmvfh-2021-0065
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of gender-specific challenges during and after military service on female UK Veterans

Abstract: LAY SUMMARY Currently, research on the experiences and challenges of being female in the UK Armed Forces is lacking. The current study aimed to explore some of the challenges and obstacles women have experienced both during their military service and as Veterans. In total, 750 female Veterans from the army were surveyed on their experiences during their military service and as Veterans and on their current physical and mental health problems. The results indicate that women experience several gender-based cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This was interesting given that research has shown female veterans are more likely to seek support and treatment than their male counterparts (Jones et al, 2019). However, studies have shown that women reported feeling less welcomed to veteran mental health organizations (Baumann et al, 2022; Thomas et al, 2017), and therefore they may have sought help elsewhere. Despite this, previous literature has reported females in the U.K. Armed Forces are less at risk of experiencing mental health difficulties (Fear et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was interesting given that research has shown female veterans are more likely to seek support and treatment than their male counterparts (Jones et al, 2019). However, studies have shown that women reported feeling less welcomed to veteran mental health organizations (Baumann et al, 2022; Thomas et al, 2017), and therefore they may have sought help elsewhere. Despite this, previous literature has reported females in the U.K. Armed Forces are less at risk of experiencing mental health difficulties (Fear et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…less welcomed to veteran mental health organizations (Baumann et al, 2022;Thomas et al, 2017), and therefore they may have sought help elsewhere. Despite this, previous literature has reported females in the U.K. Armed Forces are less at risk of experiencing mental health difficulties (Fear et al, 2010).…”
Section: Strengths and Limitationsmentioning
confidence: 99%